2022
DOI: 10.1111/mec.16820
|View full text |Cite
|
Sign up to set email alerts
|

Sexual interference revealed by joint study of male and female pollination success in chestnut

Abstract: Most seed plants produce both pollen and ovules. In principle, pollen export could interfere with pollen import through self‐pollination, resulting in ovule usurpation and reduced fruit set. Evidence for such interference exists under experimental settings but its importance under natural conditions is unknown. To test for sexual interference in nature, it is necessary to study together mating system, through paternity analyses, and fruit set, the proportion of flowers giving seeds or fruits. We developed a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 105 publications
1
31
0
Order By: Relevance
“…Self-pollination in cosexual chestnut trees is massive, a likely consequence of huge pollen production and frequent geitonogamy in this large mass-flowering tree. In the study site, we previously estimated, using a spatially explicit mixed mating model, that the self-pollination rate is 74% (Larue et al 2022). Hasegawa et al (2009) found even higher values of self-pollination in Japanese chestnut by genotyping pollen grains directly collected on stigmas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Self-pollination in cosexual chestnut trees is massive, a likely consequence of huge pollen production and frequent geitonogamy in this large mass-flowering tree. In the study site, we previously estimated, using a spatially explicit mixed mating model, that the self-pollination rate is 74% (Larue et al 2022). Hasegawa et al (2009) found even higher values of self-pollination in Japanese chestnut by genotyping pollen grains directly collected on stigmas.…”
Section: Discussionmentioning
confidence: 99%
“…Chestnut trees are monoecious, self-incompatible, and duodichogamous, all mechanisms frequently interpreted as adaptations to promote outcrossing (Lloyd & Webb, 1986; Webb & Lloyd, 1986; Bertin & Newman, 1993; Routley et al ., 2004; Koelling & Karoly, 2007). In a previous study, we found self-fertilization rates of 5% in chestnut trees with fully developed stamens and 1% in trees with dysfunctional stamens (Larue et al ., 2022). Even with strong inbreeding depression, this difference cannot explain the maintenance of gender dimorphism.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations